THE ANALYSIS OF DECLINING OUTPATIENT VISITS IN SURABAYA SURGICAL HOSPITAL USING AN INTERNAL BUSINESS PROCESS PERSPECTIVE - Fina Aprilia (Universitas Airlangga, 2020)
Patient visitation is one of the hospital performance indicators. There are several factors which influence the decrease of patient visitation in a hospital. This study aims to identify the factors that caused the decrease of outpatient visitations at Surabaya Surgical Hospital based on the internal business process perspective. This study used a quantitative research method which used a cross-sectional design and descriptive approach. The participants of the checklist sheet-based interview involved health assurance, marketing, human resources, outpatients, and emergency room, while the questionnaire-based interview involved 79 outpatients and 23 employees at Surabaya Surgical Hospital. The research variables included innovation development, operational process, and customer management processes (marketing). The results showed that there was one variable that had a lesser average value, i.e., the customer management processes variable (marketing) with a poor average value (2.49). Particularly, the indicators which had the lowest score from the others on average were promotion and communication. In conclusion, the decrease of outpatient visitation at Surabaya Surgical Hospital was caused by one variable with lesser average value, i.e., the customer management processes (marketing) on the promotion and communication indicator. This is because the promotions advertised by the hospitals are not much known by the society.Keywords: internal business process, outpatients, Surabaya Surgical Hospital